Ratification vote on taxonomic proposals to the International Committee on Taxonomy of Viruses (2016). - Adams, M; Lefkowitz, E; King, A; Harrach, B; Harrison, R; Knowles, N; Kropinski, A; Krupovic, M; Kuhn, J; Mushegian, A; Nibert, M; Sabanadzovic, S; et al. (Springer, 2016)
This article lists the changes to virus taxonomy approved and ratified by the International Committee on Taxonomy of Viruses (ICTV) in April 2016.